Preoperative imaging of gastric GISTs underestimates pathologic tumor size: A retrospective, single institution analysis. Issue 1 (15th April 2021) - Apte, Sameer S.; Radonjic, Aleksandar; Wong, Boaz; Dingley, Brittany; Boulva, Kerianne; Chatterjee, Avijit; Purgina, Bibiana; Ramsay, Timothy; Nessim, Carolyn
Abstract: Background: How well imaging size agrees with pathologic size of gastric gastrointestinal stromal tumors (GISTs) is unknown. GIST risk stratification is based on pathologic size, location, and mitotic rate. To inform decision making, the size discrepancy between imaging and pathology for gastric GISTs was investigated. Methods: Imaging and pathology reports were reviewed for 113 patients. Bland–Altman analyses and intraclass correlation (ICC) assessed agreement of imaging and pathology. Changes in clinical risk category due to size discrepancy were identified. Results: Computed tomography (CT) ( n  = 110) and endoscopic ultrasound (EUS) ( n  = 50) underestimated pathologic size for gastric GISTs by 0.42 cm, 95% confidence interval (CI): (0.11, 0.73), p  = 0.008 and 0.54 cm, 95% CI: (0.25, 0.82), p  < 0.001, respectively. ICCs were 0.94 and 0.88 for CT and EUS, respectively. For GISTs ≤ 3 cm, size underestimation was 0.24 cm for CT ( n  = 28), 95% CI: (0.01, 0.47), p  = 0.039 and 0.56 cm for EUS ( n  = 26), 95% CI: (0.27, 0.84), p  < 0.0001. ICCs were 0.72 and 0.55 for CT and EUS, respectively. Spearman's correlation was ≥0.84 for all groups. For GISTs ≤ 3 cm, 6/28 (21.4% p  = 0.01) on CT and 7/26 (26.9% p  = 0.005) on EUS upgraded risk category using pathologic size versus imaging size. No GISTs ≤ 3 cm downgraded risk categories. Size underestimation persisted for GISTs ≤ 2 cm on EUS (0.39 cm, 95% CI: [0.06, 0.72], p  = 0.02, post hoc analysis). Conclusion: Imaging, particularly EUS, underestimates gastric GIST size. Caution should be exercised using imaging alone to risk‐stratify gastric GISTs, and to decide between surveillance versus surgery. Highlights: Imaging underestimates gastric GIST size. This is effect is persistent at smaller sizes (≤3cm), and more pronounced on EUS. Size underestimation leads to incorrect preoperative risk‐stratification. Caution should be exercised when using imaging alone to risk stratify gastric GISTs.